2023
DOI: 10.3389/fmed.2023.1218051
|View full text |Cite
|
Sign up to set email alerts
|

Associations between smoke exposure and kidney stones: results from the NHANES (2007–2018) and Mendelian randomization analysis

Yong Huang,
Hexi Wang,
Chengwei Xu
et al.

Abstract: PurposeIt is currently controversial whether smoke exposure is associated with the risk of kidney stones. Herein, publicly available databases were combined to explore relationships with the risk of nephrolithiasis in terms of smoking status and serum cotinine concentrations.Materials and methodsFirst, we conducted an observational study using data from 2007 to 2018, based on the National Health and Nutrition Examination Survey (NHANES) database. Univariate analysis, multivariate logistic regression, trend tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that factors such as diet, physical activity, smoking, and sleep quality are associated with the risk of kidney stones, and our study further emphasizes the necessity of comprehensive assessment of these behaviors. For example, adequate fluid intake, balanced dietary structure, [ 22 ], moderate physical activity [ 23 ], smoking cessation[ 24 ], and maintaining normal sleep time are considered effective measures to reduce the risk of kidney stones [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that factors such as diet, physical activity, smoking, and sleep quality are associated with the risk of kidney stones, and our study further emphasizes the necessity of comprehensive assessment of these behaviors. For example, adequate fluid intake, balanced dietary structure, [ 22 ], moderate physical activity [ 23 ], smoking cessation[ 24 ], and maintaining normal sleep time are considered effective measures to reduce the risk of kidney stones [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the National Health and Nutrition Examination Survey (NHANES) database study, current smokers exhibited a significantly higher risk of developing kidney stones compared to non-smokers, with an odds ratio of 1.17 (95% CI: 1.04–1.31, p = 0.009), and a positive trend in risk was also noted. Additionally, individuals with serum cotinine levels ranging from 0.05 to 2.99 ng/mL showed an increased risk of nephrolithiasis with an OR of 1.15 (95% CI: 1.03–1.29, p = 0.013) [ 82 ]. The present research also indicates a significant link between passive smoking and an increased risk of kidney stone formation.…”
Section: Modifiable Lifestyle Factors and Habitsmentioning
confidence: 99%